Communication satisfaction and their relationship with organizational commitment : a study on teachers teaching at International Islamic School (IIS) - Sugiati, Lilik (Institute of Education, International Islamic University Malaysia, 2014)
This study analyzed communication satisfactions and their relationships with organizational commitment of teachers teaching at the International Islamic School (IIS). The objectives of this study was to examine the teacher's level of satisfaction on school communication based on the following aspects: (a) satisfaction with communication climate, (b) satisfaction with communication with the people in management, (c) satisfaction with organizational integration, (d) satisfaction with media quality, (e) satisfaction with horizontal and informal communication, (f) satisfaction with organizational perspective, and (g) satisfaction with personal feedback. It also examined the differences between teacher's level of satisfaction on school communication based on selected demographic variables namely; nationality and years of experience. The last aim of this study was to examine the relationship between teacher's level of satisfaction on school communication and teacher's organizational commitment. The present research used a modified questionnaire from the Communication Satisfaction Questionnaire (CSQ) which was adapted from Downs and Hazen in 1977. The questionnaire was administered to 52 teachers at the International Islamic School. A 5-point Likert scale was used to measure the teacher's level of satisfaction on school communication. Descriptive and inferential statistics were used to analyze the data. This study found that satisfactions of teachers with communications in school are moderate in all aspects. Based on nationality, the results found that there was no significant difference in teacher's satisfactions on all dimensions of communication among teachers of different nationality, except only communication satisfaction with people in management. The findings also found that there was no significant difference in teachers' satisfactions in all dimensions of communication satisfaction among teachers with different years of experience, except for satisfactions with media quality. Lastly, by using co-relational analysis, the study found that there were significant relationships between all aspects of communication satisfactions and teachers' organizational commitment. In conclusion, this study also provided conclusions and recommendations for improvements in school communications as one of the important aspect in a school system.